Analisis Hubungan Tingkat Pencahayaan, Reflektansi, dan Kekontrasan Area Kerja terhadap Keluhan Eye Strain pada Karyawan Office di PT. X Tahun 2023 - Fadhila, Afni; Tejamaya, Mila (UI Scholars Hub, 2023)
Eye strain is a condition where the eyes are strained due to prolonged overuse, especially in computer-based activities. NIOSH states that about 75 - 90% of computer users who spend three hours or more complaining of visual impairment. A study by Kowalska et al (2011) on office workers who use computers intensely stated that the prevalence of eye strain in female workers was 50,7% and in men was 32,6%. This study aims to determine the relationship between illuminance, reflectance, and work area contrast on eye strain complaints in office employees at PT. X. This research was conducted from April - June 2023 with a total sample of 134 employees by simple random sampling. The design used in this research is cross-sectional and data collection is carried out by distributing questionnaires, which were adopted from Haeny (2009) and Ramadhani (2012), and direct measurements using a lux meter. Results showed that there were 113 employees (84,3%) complaining of eye strain with the most common symptom felt by them was tension in the neck and shoulders (43,3%) and the least common symptom was pain in the eyelids (8,2%). The results of bivariate analysis showed that there was a relationship between illuminance (p-value = 0,000), reflectance (p-value = 0,001), contrast (p-value = 0,027), work duration (p-value = 0,000), and age (p-value = 0,022), but there was no relationship between visual impairment (p-value = 0,749) and history of eye health problems (p-value = 0,918) to eye strain complaints.